Factors that affect the use of public marketplaces : (case studes on the importance and factors that affect the use of government-established marketplaces in Dili, Timor-Leste : a thesis presented in fulfillment of the requirements for the Masterate in International Development Studies at Massey University, Palmerston North, New Zealand - Dos Santos, Herdade Boavide (Massey University, 2015)
Since Timor-Leste became independent in 2002, the government has made a number of significant efforts to improve the living conditions of the people. Among the efforts is the initiative for establishing or building public marketplaces throughout the country, including in Dili, the capital city of Timor-Leste. Through these public marketplaces, the government expects that people, especially lower income earners, and the poor, will engage in basic economic activities that eventually contribute to better their social and economic life. Despite this well intentioned initiative, many of these public marketplaces have been observed to be underused. Indeed, in Dili, a number of local media reported or raised the issue of vendors’ and buyers’ dissatisfaction and abandonment of government-established public markets, particularly over the past four years. This study, hence, intends to find out what has been actually going on. By focusing on two government-established marketplaces in Dili as qualitative case studies, this study explored market stakeholders’ perceptions on the importance of a public marketplace and factors that may affect the use of such a market. Specifically, this study investigated market stakeholders’ views regarding the government’s initiative for establishing or building public marketplaces, the factors that affect the use of a public marketplace, and how vendors and buyers were involved or participated in the planning process for establishing public marketplaces. This study has found that market stakeholders in general welcomed the government’s initiative for establishing a public marketplace for various reasons. A public marketplace can serve important functions such as a source of livelihood and economic income, particularly for lower income earners and the poor. Dili’s public marketplaces have also provided a mechanism for strengthening, or promoting public order and hygiene, and can be used as a means for pubiic meeting, public education and promoting social cohesion. This study also discovered various factors that affected the use of public marketplaces in Dili. These factors include non-strategic location of public marketplaces: they are far from the population centers and the main roads, and poor transport options. There had been a lack of basic facilities, such as water, electricity and toilets. The security situation in public marketplaces had been non-conducive for doing transactions; procedures for accessing vending stalls in public markets had been unclear and issues of corrupt officials. Furthermore, the vendors’ attitude and custom of selling practices and no participation of vendors and buyers in the planning process for establishing a public marketplace also affected the use of a public marketplace. Based on the findings and discussion, the study concludes that the presence of the government’s public marketplace is important as it has values economically, socially and environmentally. The study also concludes that the interdependences of market facilities (for example, availability of running water, electricity and toilet), location or distance of a market to vendors and buyers, clear regulations, better management, and the involvement of stakeholders, particularly vendors in the planning process for establishing a public marketplace should become the principal guidance in order to optimize the effectiveness of a public marketplace. By taking into consideration these important principles, the problems of abandonment of a public marketplace may be prevented.